2005
DOI: 10.1002/cbic.200400457
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Inhibition of Transcription Start by Targeting with 2′‐OMe Pentaribonucleotides Comprising Locked Nucleic Acids and Intercalating Nucleic Acids

Abstract: Inhibition of gene expression has been achieved by targeting the open complex formed during transcription initiation with short, pentameric, modified oligonucleotides.[1] This approach is an alternative to double-stranded (ds) DNA targeting by using triplex-forming oligonucleotides, in which longer probes (> 10 nucleotides) are required for high-affinity binding and specificity.[2] A local opening of the dsDNA by RNA polymerase at the start of transcription is the key to the sequence-selective[a] Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…LNAs were designed to be complementary to sequences at the transcription start site and to regions further upstream or downstream. Pedersen and colleagues had previously shown that LNA pentanucleotides could block transcription by E. coli polymerase in cell free assays (26), a result similar to that achieved in classic studies by Sigman and coworkers using RNA pentanucleotides (27).…”
Section: Design Of Lnassupporting
confidence: 70%
“…LNAs were designed to be complementary to sequences at the transcription start site and to regions further upstream or downstream. Pedersen and colleagues had previously shown that LNA pentanucleotides could block transcription by E. coli polymerase in cell free assays (26), a result similar to that achieved in classic studies by Sigman and coworkers using RNA pentanucleotides (27).…”
Section: Design Of Lnassupporting
confidence: 70%
“…Duplexes with other interstrand zipper arrangements of X monomers only exhibit marginal signal intensity at 495 nm (results not shown). Pyrene emission signals at 495 nm are routinely attributed to pyrene-pyrene excimers41,42,45,5155, suggesting that the pyrene moieties of the two X monomers comprising the energetic hotspots in Invader LNA probes are separated by ~3.4 Å56 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Examples include minor groove binding polyamides21, TFOs capable of recognizing all four Watson-Crick base pairs via the major groove22,23, optimized PNAs24,25, antigene (ag) PNA26,27, agLNA28,29, “Zorro” LNA30, pseudo-complementary (pc) DNA31,32, pcPNA33–38, and other approaches3941. While these emerging probe strategies are promising, there remains a need for a probe technology that allows fast, efficient and specific dsDNA targeting at physiologically relevant ionic strengths with minimal sequence restrictions and uncomplicated “DNA-like” handling (adequate aqueous solubility, compatibility with delivery agents).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a correlation between the thermal stability and the formation of an excimer band. Thus, T m values of duplexes showing an excimer band ( ON14 / ON22 ,52, 53 ON18 / ON26 , and ON20 / ON27 ) are higher than the T m values of duplexes with no excimer band in fluorescence spectra ( ON15 / ON23 , ON16 / ON24 , and ON17 / ON25 ). This means that proper interstrand overlapping/stacking of pyrene residues as a pseudo‐pair in the middle of the DNA duplex results in the formation of an excimer band.…”
Section: Resultsmentioning
confidence: 83%
“…We have recently observed that placing two INA monomers opposite each other in the duplex led to the formation of so‐called easily denaturing nucleic acids53, 54 in which each of the INA sequences has a preference in binding to the complementary unmodified DNA of the same length rather than forming a duplex with each other 26. 52, 53 A similar tendency was observed for o TINA with 1‐ethynylpyrene, that is, the duplex with an inserted pair of 5 ( ON18 / ON26 ) had lower T m (42.0 °C) than duplexes with the complementary DNA molecules ( ON18 / ON21 and ON26 / ON13 with T m of 46.5 and 44.5 °C, respectively). None of the duplexes with a bulged pair of intercalators in the middle of the sequence showed an increased thermal stability in comparison with the wild‐type duplex.…”
Section: Resultsmentioning
confidence: 99%